Induction of long-term potentiation at spinal synapses by noxious stimulation or nerve injury - Sandkühler, Jürgen; Liu, Xianguo (European journal of neuroscience, 1998)
Use-dependent long-term potentiation of synaptic strength (LTP) is an intensively studied model for learning and memory in vertebrates. Induction of LTP critically depends on the stimulation parameters of presynaptic fibres with synchronous high-frequency bursts being most effective at many central synapses. It is, however, not known whether naturally occurring discharge patterns may induce LTP and whether LTP has any biological function in sensory systems. Here we have investigated the LTP of excitatory synaptic transmission between primary afferent C-fibres, many of which are nociceptors, and neurons in rat superficial spinal dorsal horn. LTP that lasted for 4-6 h could not only be induced by electrical stimulation of sural nerve but also by natural stimulation of heat-, mechano- or chemosensitive nociceptors in the skin or by acute nerve injury. Maintenance of LTP was not affected when afferent nerves were cut 1 h or 5 min after noxious skin stimulation, indicating that an ongoing afferent barrage is not required. Natural noxious stimuli induced LTP in animals which were spinalized but were ineffective in intact animals. Thus, induction of LTP is suppressed by tonically active supraspinal descending systems. We conclude that the natural non-synchronized discharge patterns that are evoked by noxious stimulation may induce LTP and that this new form of LTP may be an underlying mechanism of afferent induced hyperalgesia.
Published: 25 December 2001
Gesehen am 03.05.2021